Impact of sex on prognostic host factors in surgical patients with lung cancer. Issue 12 (14th September 2016) - Wainer, Zoe; Wright, Gavin M.; Gough, Karla; Daniels, Marissa G.; Choong, Peter; Conron, Matthew; Russell, Prudence A.; Alam, Naveed Z.; Ball, David; Solomon, Benjamin
Abstract : Background: Lung cancer has markedly poorer survival in men. Recognized important prognostic factors are divided into host, tumour and environmental factors. Traditional staging systems that use only tumour factors to predict prognosis are of limited accuracy. By examining sex‐based patterns of disease‐specific survival in non‐small cell lung cancer patients, we determined the effect of sex on the prognostic value of additional host factors. Methods: Two cohorts of patients treated surgically with curative intent between 2000 and 2009 were utilized. The primary cohort was from Melbourne, Australia, with an independent validation set from the American Surveillance, Epidemiology and End Results (SEER) database. Univariate and multivariate analyses of validated host‐related prognostic factors were performed in both cohorts to investigate the differences in survival between men and women. Results: The Melbourne cohort had 605 patients (61% men) and SEER cohort comprised 55 681 patients (51% men). Disease‐specific 5‐year survival showed men had statistically significant poorer survival in both cohorts ( P  < 0.001); Melbourne men at 53.2% compared with women at 68.3%, and SEER 53.3% men and 62.0% women were alive at 5 years. Being male was independently prognostic for disease‐specific mortality in the Melbourne cohort after adjustment for ethnicity, smoking history, performance status, age, pathological stage and histology (hazard ratio = 1.54, 95% confidence interval: 1.10–2.16, P  = 0.012). Conclusions: Sex differences in non‐small cell lung cancer are important irrespective of age, ethnicity, smoking, performance status and tumour, node and metastasis stage. Epidemiological findings such as these should be translated into research and clinical paradigms to determine the factors that influence the survival disadvantage experienced by men.